Inovasi Bahan Ajar IPA Berupa Ensiklopedia Berbasis TPACK untuk Pembelajaran yang Bermakna - A’yun, Dya Qurotul; Rosa, Friska Octavia (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Science (IPA) learning is crucial in shaping students' understanding of the environment and nature, and in preparing the younger generation to preserve environmental sustainability. However, the delivery of science material often lacks engagement, necessitating innovative teaching materials to enhance student comprehension and learning outcomes. Encyclopedia-based teaching materials, with their comprehensive, systematic, and illustrated content, are considered effective in attracting interest and clarifying concepts. Furthermore, integrating Technological Pedagogical and Content Knowledge (TPACK) into science learning is vital to prepare students for mastering technology in the digital age. This preliminary study aims to analyze the urgency and potential of developing TPACK-based encyclopedia science teaching materials to improve student learning outcomes. The research employed a literature review (library research) method by examining various relevant references. The findings indicate that the development of TPACK-based encyclopedia science teaching materials is highly necessary as it can enrich students' learning experiences, create more engaging and relevant learning, and foster students' technological literacy and critical thinking skills to face future.